PRELIMINARY ANALYSIS KESULITAN MAHASISWA S-1 PGSD DALAM MEREVIEW ARTIKEL ILMIAH DI JURNAL - Muhammad Syazali; Lalu Hamdian Affandi; Nursaptini Nursaptini; Aisa Nikmah Rahmatih; Fitri Puji Astria (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Mataram, 2020)
Reviewing scientific articles published in journals is a competency needed by students to improve their writing skills. As a form of implementation of Higher Education Tri Dharma in the field of education, lecturers are responsible for training students to review articles. To provide optimal learning facilities, information is needed related to student difficulties in reviewing articles in journals. This study aims to diagnose the difficulties of undergraduate students at PGSD FKIP Mataram University in reviewing scientific articles in journals. The study was conducted on S1 students of PGSD FKIP Mataram University who programed Quantitative Research Methods courses. The research subject of 36 students was determined using a purposive sampling technique. Data collection is done by assigning students to review 1 scientific article published by a SINTA accredited journal. The results of the review by students were analyzed descriptively to determine the location of student difficulties. The results showed that the largest proportion of student difficulties lies in the research method (86.11%), then the research problem (44.44%), and the smallest proportion is the research result (5.56%). Information from the results of this study can be used as a reference for providing learning facilities to improve student review skills. This skill can help students in completing theses which have been a problem for many undergraduate students at PGSD FKIP Mataram University.